2016
DOI: 10.1210/jc.2016-3445
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Insulinoma Using 68Ga-DOTATATE PET/CT Scan

Abstract: Context. The reliable localization of insulinoma is critical for the successful surgical treatment.Objective. This study compared the accuracy of 68 Gallium (Ga)-DOTATATE PET/CT to anatomic imaging modalities, selective arterial secretagogue injection (SASI), and intraoperative ultrasound (IOUS) and palpation for localizing insulinoma in patients who were biochemically cured. Design, Setting, and Patients. We conducted a retrospective analysis of 31 patients who had an insulinoma confirmed on histology and wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(57 citation statements)
references
References 19 publications
(19 reference statements)
2
44
0
3
Order By: Relevance
“…The sensitivity for detecting insulinomas has been reported to be approximately 75% for CT and 55–90% with MRI imaging . EUS has been reported to have excellent sensitivity (85–95%); however, insulinomas are often located in regions of the pancreas which makes them more difficult to visualize . SACST is the most invasive localizing procedure, however has been reported as the most sensitive modality (95–100%) .…”
Section: Discussionmentioning
confidence: 67%
“…The sensitivity for detecting insulinomas has been reported to be approximately 75% for CT and 55–90% with MRI imaging . EUS has been reported to have excellent sensitivity (85–95%); however, insulinomas are often located in regions of the pancreas which makes them more difficult to visualize . SACST is the most invasive localizing procedure, however has been reported as the most sensitive modality (95–100%) .…”
Section: Discussionmentioning
confidence: 67%
“…Conventional imaging modalities have variable success in localisation of insulinoma, with reported accuracy from a contemporary study demonstrating sensitivity of abdominal CT (64%) and magnetic resonance imaging (MRI) (75%) (Druce et al 2010). Endoscopic ultrasound (EUS) (65-94%) and SACST (63-94%) are highly operator dependent and the latter is particularly invasive and is only able to identify the pancreatic region of the tumour (McLean 2004, Guettier et al 2009, Druce et al 2010, Nockel et al 2017. The opportunity for biopsy confirmation of insulinoma is an advantage of EUS.…”
Section: Insulinomamentioning
confidence: 99%
“…However, a recent retrospective review of pathologically confirmed insulinoma demonstrated successful localisation in 9/10 cases using this modality (Nockel et al 2017). Another retrospective review of 13 patients with histopathological correlation of hyperinsulinaemic hypoglycaemia (eight benign insulinoma, two malignant insulinoma and three nesidioblastosis) demonstrated positive SSTR PET/ CT ( 68 Ga-DOTATATE or 68 Ga-DOTA-TOC) in 11/13 patients (Prasad et al 2016, 8).…”
Section: Somatostatin Receptor Imagingmentioning
confidence: 99%
“…If these studies are negative, more invasive techniques, such as selective angiography with intra-arterial calcium stimulation and hepatic venous sampling for insulin levels, localize >80% of insulinomas (Brown et al 1997, Guettier et al 2009). Additionally, new somatostatin receptor (SSTR)-targeting PET modalities, such as 68Gallium-DOTATATE, are adjunct modalities for localization , Nockel et al 2017. As insulinomas express glucagon-like peptide 1 (GLP1) receptor more than SSTR, PET imaging with labeled GLP1 analogs might be a promising tool (Antwi et al 2015).…”
Section: Other Functional Duodeno-pancreatic Netsmentioning
confidence: 99%